1982
DOI: 10.1111/j.1399-3054.1982.tb00253.x
|View full text |Cite
|
Sign up to set email alerts
|

The activity and interaction of brassinolide and gibberellic acid in mung bean epicotyls

Abstract: 1982. The activity and interaction of brassinolide and gibberellic acid in mung bean epieotyls. -Physiol. Plant. 54: 239-243.The growth rate of mung bean epicotyls was used for evaluating the effect of brassinolide on cell elongation. Growth above that of control plants was observed at 10"^*' M and above. Gibberellic acid showed an additivity relationship with low concentrations (10"' -10~* M) of brassinolide in this test system and the two growth promoters may therefore act independently at the cellular level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 18 publications
3
26
0
1
Order By: Relevance
“…Many of their effects are at hypocotyls elongation, as in the case of beans (Gregory and Mandava, 1982), pea (Clouse and Zurek, 1991) and radish (Takatsuto, 1994), which is consistent with the results in the present research. Although a few have been works in which BRs has been used as growth regulators on in vitro culture, the effects show in this study were similar to those observed on hypocotyls of chile peppers, where 24-epi-brassinolide, a brassinolide analogous, stimulated the development of stems when it was used alone, whereas its effect was inhibited when combined with zeatin or gibberellin (GA 3 ) (Franck-Duchenne et al, 1998).…”
Section: Elongaci贸n De Brotessupporting
confidence: 82%
“…Many of their effects are at hypocotyls elongation, as in the case of beans (Gregory and Mandava, 1982), pea (Clouse and Zurek, 1991) and radish (Takatsuto, 1994), which is consistent with the results in the present research. Although a few have been works in which BRs has been used as growth regulators on in vitro culture, the effects show in this study were similar to those observed on hypocotyls of chile peppers, where 24-epi-brassinolide, a brassinolide analogous, stimulated the development of stems when it was used alone, whereas its effect was inhibited when combined with zeatin or gibberellin (GA 3 ) (Franck-Duchenne et al, 1998).…”
Section: Elongaci贸n De Brotessupporting
confidence: 82%
“…42,43 However, it is poorly understood whether BRs cross-talk with GAs. Previous physiological studies have pointed out that BRs and GAs enhance plant growth in an additive manner, 44 indicating that the two hormones may act independently at the cellular level.…”
Section: Brassinosteroids and Gibberellinsmentioning
confidence: 99%
“…Of the many physiological effects brassinosteroids have on plants, cell elongation is perhaps the best documented. Brassinosteroids promote elongation of soybean (Glycine max), mung bean, azuki bean, and pea epicotyls Gregory and Mandava, 1982;Mandava, 1988;Clouse et al, 1992); bean, sunflower, and cucumber hypocotyls Katsumi, 1985); Arabidopsis peduncles (Clouse et al, 1993); and maize mesocotyls and wheat coleoptiles Sasse, 1985). Despite numerous physiological studies, the molecular mechanism of brassinosteroid-induced elongation remains unclear.…”
mentioning
confidence: 99%